2021
DOI: 10.1017/s0144686x20002007
|View full text |Cite
|
Sign up to set email alerts
|

A multiple perspective view of personhood in dementia

Abstract: Personhood has been a key influence on the development of person-centred care models in dementia. However, there is ambiguity around the concept and interpretation of personhood, and what it means in practical terms for the delivery of care to people with dementia. This study examines the conceptualisation of personhood within the formal care system for people with dementia in Ireland. A multiple perspective study design examines the experiences of personhood in dementia from the perspectives of people with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Additionally, Harmer and Orrell [18] reported that staff lacked sufficient skills in identifying and delivering activities that residents with dementia could engage in. More recent evidence has identified numerous barriers of implementing person-centred care in practice, which include issues such as time constraints, staff turnover, negative attitudes, poor relationships, lack of consistency in care personnel, a lack of understanding of dementia, and a lack of autonomy and empowerment towards residents [20][21][22][23]. With the large prevalence of people living with dementia and importance of supporting personhoodespecially in later stages of the disease it is necessary to investigate ways in which care staff can be supported in providing person-centred care through meaningful interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Harmer and Orrell [18] reported that staff lacked sufficient skills in identifying and delivering activities that residents with dementia could engage in. More recent evidence has identified numerous barriers of implementing person-centred care in practice, which include issues such as time constraints, staff turnover, negative attitudes, poor relationships, lack of consistency in care personnel, a lack of understanding of dementia, and a lack of autonomy and empowerment towards residents [20][21][22][23]. With the large prevalence of people living with dementia and importance of supporting personhoodespecially in later stages of the disease it is necessary to investigate ways in which care staff can be supported in providing person-centred care through meaningful interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Findings demonstrate that participants did not report changes to their current self or feelings of discontinuity to their past self, expressing that they feel they are the same person as before the onset of dementia (Borley et al, 2016;Caddell & Clare, 2011;Caradec & Chamahian, 2017;Hennelly & O'Shea, 2021;MacRae, 2010;Borley & Hardy, 2017). The few longitudinal qualitative studies identified (Johannessen et al, 2018;Steeman et al, 2013) did not report substantial alterations to participants' self; minor changes were described, mostly everyday difficulties and cognitive challenges, but people with dementia do not feel that they have changed in a major way.…”
Section: Perceived Changementioning
confidence: 82%
“…Better understanding of alterations in selfhood, ensuring that people's experiences are not undermined by perceptions of total loss, is key to address psychological symptoms of people living with dementia as well as to inform new pathways for dementia care interventions. Person-centered psychological care can only be achieved by recognising the centrality of selfhood in people's wellbeing and quality of life (Hennelly et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to provide continuity during a move, residents should be provided with choice, and the need for care should be balanced with supporting independence. This is integral not only to achieving PCC in LTRC, but also in maintaining resident QoL ( Barnes et al., 2013 ; Baxter et al., 2019 ; Edvardsson et al., 2010 ; Hennelly & O’Shea, 2021 ).…”
Section: Resultsmentioning
confidence: 99%